EFEKTIVITAS MODEL PEMBELAJARAN INTERAKTIF DENGAN PERTANYAAN PENGARAH (PROMPTING QUESTION) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII SMP NEGERI 2 LUBUK PAKAM - Zalmi Zalmi; Dian Angraini (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This research is a type of classroom action research (PTK). The problem in this study is whether the application of the interactive learning model with prompting questions is effective in improving the mathematics learning outcomes of class VIII students of SMP Negeri 2 Lubuk Pakam on the subject matter of the Coordinate System? The purpose of this study was to determine whether or not the interactive learning model was effective with prompting questions to improve the mathematics learning outcomes on the subject matter of the Coordinate System. Based on the data analysis, it can be concluded that in cycle 1 the students' learning completeness in this material is only 65.50 while in cycle 2 by applying the interactive learning model learning strategy with prompting questions, it increases in cycle 2 the average value increases. to 87.89. Student response also increased, data from observations of student activity from 60.42% in cycle 1, increased in cycle 2 to 87.50%. This means that the average mathematics learning outcomes taught by interactive learning models with prompting questions are greater than the average mathematics learning outcomes taught by conventional learning methods. Based on the results of the research and discussion, it can be concluded that the average test results of the experimental class are greater than the control class so that it can be said that the interactive learning model with prompting questions is effective for improving the mathematics learning outcomes. Expertise on the main material of the Coordinate System, and it is recommended that teachers continue to develop interactive learning models with prompting questions and apply it to other subject matter learning